Ultraviolet Filters for Cosmetic Applications - Georgiana Nitulescu; Dumitru Lupuliasa; Ines Adam-Dima; George Mihai Nitulescu (Cosmetics, 2023)
Sunscreens reduce the occurrence risk of skin disorders such as sunburn, skin aging, and cancer through their ability to absorb, reflect, and scatter ultraviolet (UV) radiation. This review provides an overview of UV filters as active ingredients of sunscreen products, emphasizing their classification and structural characteristics. Their photostability, mechanism of action of ultraviolet radiation absorption, optical properties, and regulatory status are discussed based on their chemical structure. The main classes of organic UV filters presented include aminobenzoic acid derivatives, salicylic acid derivatives, cinnamic acid derivatives, benzophenones, dibenzoylmethane derivatives, benzylidene camphor derivatives, triazines, benzimidazole derivatives, and benzotriazole derivatives. The pursuit of new UV filters through research is crucial in advancing sunscreen technology and ensuring the availability of effective and safe options for sun protection.